1992
DOI: 10.1177/000331979204300606
|View full text |Cite
|
Sign up to set email alerts
|

Skin Flow The Venoarteriolar Response and Capillary Filtration in Diabetics. A 3-year Follow-Up

Abstract: Resting skin blood flow (RF) and the venoarteriolar response (VAR = the vasoconstrictor response on standing) have been studied in 100 patients with diabetic neuropathy, in 100 diabetics without neuropathy, and in 100 normal subjects by laser Doppler flowmetry. Capillary filtration was also studied with strain gauge plethysmography. The authors followed up these patients by evaluating their microcirculation again after three years. At the beginning of the study in patients with neuropathy, RF and capillary fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(92 citation statements)
references
References 9 publications
(1 reference statement)
3
88
1
Order By: Relevance
“…The present patient did not have congestive heart failure, arrhythmia or hypotension and had not taken vasoconstrictive drugs. However, our patient did have diabetic neuropathy, probably inducing abnormal microcirculation (8). Abnormalneurogenic regulation of microvascular haemodynamicsmay contribute to the deterioration ofmesenteric microcirculation.…”
Section: Discussionmentioning
confidence: 62%
“…The present patient did not have congestive heart failure, arrhythmia or hypotension and had not taken vasoconstrictive drugs. However, our patient did have diabetic neuropathy, probably inducing abnormal microcirculation (8). Abnormalneurogenic regulation of microvascular haemodynamicsmay contribute to the deterioration ofmesenteric microcirculation.…”
Section: Discussionmentioning
confidence: 62%
“…Our results are comparable to the baseline data from the majority of other studies [7, 8, 33, 34, 35, 37, 38, 39], where BSBF in diabetic patients, although lower in absolute terms, did not differ significantly from BSBF in healthy controls. On the contrary, Belcaro et al [44]found increased resting skin blood flow in the feet of diabetic patients with neuropathy when compared to diabetic patients without neuropathy and control subjects. Similar results were obtained by Fromy et al [45], who found mean BSBF in diabetic patients without neuropathy to be similar to that in control subjects and lower than that in diabetic patients with subclinical and clinical neuropathy.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, the capability of effective precapillary vasoconstriction on standing is reduced. This exposes the capillary bed to a high hydrostatic load, producing oedema and thickening of the capillary basement membrane [43]. These stresses are thought to evoke an inflammatory response in the microvascular endothelium, with a subsequent release of extravascular matrix proteins.…”
Section: Structural Microvascular Changes In Diabetesmentioning
confidence: 99%